Analisis Determinan Ketimpangan Pendapatan di Indonesia - Aufa Oksamulya; Ali Anis (Universitas Negeri Padang, 2020)
The purpose of this research is to analyze the effect of education, foreign direct investment (FDI), and migration to income inequality in Indonesia. Using secondary data in the form of panel regression in 32 Indonesian provinces from 2014-2018 (sourced from the Central Statistics Agency). The independent variables in this test are Education (X1), Foreign Direct Investment (FDI) (X2), and migration (X3). Data is processed by panel data analysis, there are several tests on inductive analysis, namely: (1) Panel Regression Model (2) Classical Assumption Test (3) t test (4) f test. From the tests that have been done, the results show (1) that there is a significant and negative influence between education and income inequality in Indonesia. (2) there is no significant and negative influence between Foreign Direct Investment (FDI) and income inequality in Indonesia. (3) there is a significant and positive influence between migration and income inequality in Indonesia. Partially there is a significant influence between all independent variables namely education, foreign direct investment (FDI) and migration to income inequality in Indonesia at α = 5%.